2022
DOI: 10.1186/s12931-022-01980-4
|View full text |Cite
|
Sign up to set email alerts
|

LPA1 antagonist BMS-986020 changes collagen dynamics and exerts antifibrotic effects in vitro and in patients with idiopathic pulmonary fibrosis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a debilitating lung disease with limited treatment options. A phase 2 trial (NCT01766817) showed that twice-daily treatment with BMS-986020, a lysophosphatidic acid receptor 1 (LPA1) antagonist, significantly decreased the slope of forced vital capacity (FVC) decline over 26 weeks compared with placebo in patients with IPF. This analysis aimed to better understand the impact of LPA1 antagonism on extracellular matrix (ECM)-neoepitope biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…The involvement of the ENPP2-LPA-LPAR axis in inflammation and fibrosis is not new and several studies have shown its crucial participation (Tager et al, 2008;Castelino et al, 2011;Gan et al, 2011;Sakai et al, 2013;Ohashi and Yamamoto, 2015;He et al, 2018;Ninou et al, 2018); however, the mechanisms and cellular targets have been underexplored. Several ongoing studies suggest the ENPP2-LPA-LPAR axis as a prognostic indicator of injury-or radiation-induced fibrosis (NCT05031065), with some studying the safety, tolerance, and effectiveness of orally available ENPP2 inhibitors [BBT-877: NCT03830125; GLPG1690 (ziritaxestat): NCT02738801 and NCT03798366] or LPAR antagonists [BMS-986020: NCT01766817 (Decato et al, 2022); BMS-986278: NCT04308681], as a means of reducing tissue fibrosis and improving organ function in different patients cohorts. Because stromal cells of mesenchymal origin, e.g., FAPs and ASCs, highly express Lpar1, Enpp2, and key Plpp members, upcoming research should focus on better understanding the role of LPA axis in muscle homeostasis, inflammation, fibrosis, repair, and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the ENPP2-LPA-LPAR axis in inflammation and fibrosis is not new and several studies have shown its crucial participation (Tager et al, 2008;Castelino et al, 2011;Gan et al, 2011;Sakai et al, 2013;Ohashi and Yamamoto, 2015;He et al, 2018;Ninou et al, 2018); however, the mechanisms and cellular targets have been underexplored. Several ongoing studies suggest the ENPP2-LPA-LPAR axis as a prognostic indicator of injury-or radiation-induced fibrosis (NCT05031065), with some studying the safety, tolerance, and effectiveness of orally available ENPP2 inhibitors [BBT-877: NCT03830125; GLPG1690 (ziritaxestat): NCT02738801 and NCT03798366] or LPAR antagonists [BMS-986020: NCT01766817 (Decato et al, 2022); BMS-986278: NCT04308681], as a means of reducing tissue fibrosis and improving organ function in different patients cohorts. Because stromal cells of mesenchymal origin, e.g., FAPs and ASCs, highly express Lpar1, Enpp2, and key Plpp members, upcoming research should focus on better understanding the role of LPA axis in muscle homeostasis, inflammation, fibrosis, repair, and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to aberrantly high levels of LPA and overexpression of LPAR1 in IPF patients, LPAR1 inhibitor such as BMS-986020 have also been evaluated in clinical trials for the treatment of IPF [ 39 , 40 ]. A 26-week clinical trial demonstrated that treatment of IPF patients with BMS-986020 results in significant improvement in forced vital capacity (NCT01766817) [ 39 , 41 ]. However, hepatobiliary toxicity has also been reported in some patients receiving BMS-986020.…”
Section: Atx-lpar1 Gpcr Axis In Idiopathic Pulmonary Fibrosis and Cancermentioning
confidence: 99%
“…In addition, the LPA receptor antagonist BrP-LPA was studied for the treatment of BC, leading to reduced cancer cell migration and tumor regression [ 116 ]. Other ATX inhibitors such as IOA-289 and PF8380, or BMS-986020, a LPAR1 antagonist, were developed and showed promising results in preclinical and clinical trials in other conditions [ 117 , 118 , 119 , 120 ]; however, they have not yet been tested in BC. Given the importance of ATX-LPA signaling, expanding research of these novel molecules in BC could lead to new therapeutic alternatives.…”
Section: The Atx-lpa Axis As a Therapeutic Target In Bcmentioning
confidence: 99%